2016
DOI: 10.1111/ijn.12450
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction of health‐care providers with electronic health records and perceived barriers to its implementation in the United Arab Emirates

Abstract: The integration of electronic health records (EHRs) has shown promise in improving health-care quality. In the United Arab Emirates, EHRs have been recently adopted to improve the quality and safety of patient care. A cross-sectional survey of 680 health-care providers (HCPs) was conducted to assess the satisfaction of HCPs in the United Arab Emirates with EHRs' impact on access/viewing, documentation and medication administration and to explore the barriers encountered in their use. Data were collected over 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 23 publications
1
26
1
Order By: Relevance
“…The results of the study showed that the use of android-based application namely, Smart Contraception can increase the speed of acceptors' data access, efficiently managed the time in providing contraception services, and minimize the error rates. It was in line with BaniIssa et al, 2016, Carayon et al, 2015, who found that technology health documentation can improve the communication between the health care providers, efficiently managed the time in providing consultation, effieciently managed the work time of nurse, and speed up the data tracking (Bani-Issa, Al Yateem, Al Makhzoomy, & Ibrahim, 2016;Carayon et al, 2015).…”
Section: Discussionsupporting
confidence: 74%
“…The results of the study showed that the use of android-based application namely, Smart Contraception can increase the speed of acceptors' data access, efficiently managed the time in providing contraception services, and minimize the error rates. It was in line with BaniIssa et al, 2016, Carayon et al, 2015, who found that technology health documentation can improve the communication between the health care providers, efficiently managed the time in providing consultation, effieciently managed the work time of nurse, and speed up the data tracking (Bani-Issa, Al Yateem, Al Makhzoomy, & Ibrahim, 2016;Carayon et al, 2015).…”
Section: Discussionsupporting
confidence: 74%
“…Numerous studies have detected a direct association between user satisfaction and perceived usefulness of EHRS (Bani-Issa et al, 2016;Gagnon et al, 2012;Hoerbst & Schweitzer, 2015;Kruse, Kothman, et al, 2016). Lack of perceived usefulness can increase the level of resistance to a system in end-users (Kruse, Kristof, et al, 2016).…”
Section: System Efficiency and Perceived Usefulnessmentioning
confidence: 99%
“…EHRS end-user satisfaction surveys have been identified as useful tools to measure the success or failure of any EHRS implementation (Yusof et al, 2008). Consequently, several studies have examined enduser satisfaction with EHRS since 1996 (Bani-Issa et al, 2016;Khajouei et al, 2011;Lee et al, 1996).…”
Section: Study Three: Evaluation Of Implemented Ehrs In Phcs In Sa Frmentioning
confidence: 99%
See 2 more Smart Citations